Application of Telecommunications Technologies in the Management of Territories - SAVINA, Svetlana Vladimirovna; TSVETKOVA, Olga Nikolaevna; GALIMOVA, Leysan Ismagilovna; AVEZOV, Azizullo Habibovich; NAZAROV, Abdushukur Abdurahimovich (Journal of Environmental Management and Tourism; Vol 11 No 5 (2020): JEMT Volume XI Issue 5(45) Fall 2020, 2020)
Contemporary management of territories cannot be imagined without the effective use of telecommunications technologies, which create conditions for the systematic and harmonious development of territories, as well as their identification in today’s global digital space. Besides, it should be noted that the existing management systems are largely outdated and ineffective for the modern globally progressive information environment and their full functioning. Based on the conducted expert survey, the authors identified tasks of implementing telecommunications technologies in the management of rural territories, users of telecommunications technologies used when managing rural territories, opportunities for positioning rural territories through telecommunications technologies, areas for implementing telecommunications technologies in the management of rural territories, as well as presented the experience of the EU countries in the development of rural territories based on the concept of the smart village.